EXPERIENCE OF TYPE 2 DIABETES MELLITUS PATIENTS WITH NON-PHARMACOLOGICAL APPROACHES IN SUMBERSUKO VILLAGE: A QUALITATIVE STUDY - Utomo, Dhamarriyo; Dewi, Putu Ayu Sintya; Akbar, Reyhan Maulana Fila; Basukresna, Damien; Njotokusumo, Kevin; Rachmi, Siti Nurluthfia; Soenarti, Sri; Pawestri, Aulia Rahmi (Faculty of Medicine Universitas Brawijaya, 2026)
Diabetes is a major public health concern that has a detrimental impact on health and quality of life. Prior meta-analyses have shown that non-pharmacological approaches such as physical activity, nutrition, herbal medicine, and sleep quality can effectively reduce HbA1c and fasting blood glucose levels in patients with type 2 diabetes mellitus (T2DM). Unfortunately, public awareness of these strategies remains limited, leading to poor disease control, a higher risk of complications, and increased strain on the healthcare system. This study aimed to understand the experiences and perceptions of patients with type 2 diabetes in Sumbersuko Village, Malang Regency, as they managed their condition through non-pharmacological approaches. A qualitative descriptive study was conducted in Sumbersuko Village in 2024, using purposive sampling. Ten informants in this study were patients diagnosed with T2DM, with no additional interviews conducted with family members or caregivers. Data were collected through face-to-face, in-depth, and semi-structured interviews using a phenomenological method, and then analyzed using thematic analysis. Of the ten participants, eight managed their condition by controlling their nutritional intake, four used herbal medicine, and one reported poor sleep quality. Most participants engaged in physical activity, primarily low-intensity activities such as walking, with a duration of approximately 15 to 30 minutes per session. In conclusion, the integration of nutrition, physical activity, traditional medicine, and sleep quality plays a vital role in the management and prevention of T2DM, so it is necessary to highlight a holistic treatment approach.